Efficient phase-matched third harmonic generation in a metal-clad plasmonic double-slot waveguide. (30th January 2015) - Wu, Tingting; Ping Shum, Perry; Shao, Xuguang; Sun, Yunxu; Huang, Tinaye; Wei, Lei
Abstract: We propose a metal-clad plasmonic double-slot waveguide with DDMEBT integrated into the slot region as the interactive material for third harmonic generation (THG) from the mid-IR (3600 nm) to the near-IR (1200 nm) region. Typically, an efficient THG process in a waveguide platform relies on three key aspects: high third-order nonlinear susceptibility of the interactive material, fulfillment of the phase-matching condition (PMC), and large pump-harmonic modal overlap. Although it has been theoretically predicted to be possible, designing waveguides to achieve the three key aspects simultaneously is still a major challenge. In the metal-clad plasmonic double-slot waveguide, the PMC between the zeroth mode at the fundamental wave (FW) and the second mode at the third harmonic (TH) is achieved. Taking advantage of the channel plasmon polariton (CPP), the electric fields at both FW and TH are tightly confined in the slot region. The specific slot waveguide structure is exploited to significantly enhance the pump-harmonic modal overlap by greatly reducing the counteractive electric field portion of the second mode at TH. According to our simulation, THG conversion efficiency reaches 1.4732 × 10 −5 with 3 W pump power at a waveguide length of 12.3 μ m. This THG efficiency is greatly enhanced because of the high third-order nonlinear optical susceptibility of the DDMEBT, the specific plasmonic slot waveguide structure, and the CPP nature of the guided modes—it is more than two times that obtained by simply considering a single slot under the same slot-width condition.